Antibody-cytokine fusion proteins: applications in cancer therapy - Ortiz-Sánchez, Elizabeth (Expert Opin Biol Ther, 2008)
BACKGROUND: Antibody-cytokine fusion proteins consist of cytokines fused to an antibody to improve antibody-targeted cancer immunotherapy. These molecules have the capacity to enhance the tumoricidal activity of the antibodies and/or activate a secondary antitumor immune response. OBJECTIVE: To review the strategies used to develop antibody-cytokine fusion proteins and their in vitro and in vivo properties, including preclinical and clinical studies focusing on IL-2, IL-12 and GM-CSF. METHODS: Articles were found by searching databases such as PubMed and Clinical Trials of the US National Institutes of Health. RESULTS/CONCLUSION: Multiple antibody-cytokine fusion proteins have demonstrated significant antitumor activity as direct therapeutics or as adjuvants of cancer vaccines in preclinical studies, paving the way for their clinical evaluation.